“Out, out, brief candle! Life’s but a walking shadow”: 5-HTTLPR Is Associated With Current Suicidal Ideation but Not With Previous Suicide Attempts and Interacts With Recent Relationship Problems - Bokor, Janos; Krause, Sandor; Torok, Dora; Eszlari, Nora; Sutori, Sara; Gal, Zsofia; Petschner, Peter; Anderson, Ian M.; Deakin, Bill; Bagdy, Gyorgy; Juhasz, Gabriella; Gonda, Xenia (Frontiers in Psychiatry, 2020)
Background: Suicide is among the leading causes of death in adolescents and young adults, however, its neurobiological etiology is still not understood. In spite of original reports concerning the involvement of 5-HTTLPR, in interaction with recent stress in the appearance of suicidal ideation and attempts replication attempts have yielded contradictory results. In our study we analysed the association between 5-HTTLPR, lifetime suicide attempts and current suicidal ideation, hopelessness and thoughts of death as main effects and in interaction with childhood adversities, recent stress and different types of recent life events in a general population sample. Methods: 2358 unrelated European volunteers were genotyped for 5-HTTLPR, provided phenotypic data of previous suicide attempts and current suicidal ideation, hopelessness and thoughts about death and information on childhood adversities and recent life events. Logistic and linear regression models were run with age, gender and population as covariates to test for the effect of 5-HTTLPR as a main effect and in interaction with childhood adversities and recent life events on previous suicide attempts and current suicidal ideation. Benjamini-Hochberg FDR Q values were calculated to correct for multiple testing. Results: 5-HTTLPR had no significant effect on lifetime suicide attempts either as a main effect on in interaction with childhood adversities. 5-HTTLPR had a significant main effect on current suicidal ideation in the dominant model (Q=0.0344). 5-HTTLPR did not interact with childhood adversities or total number of recent life events on any phenotypes related to current suicidal risk, however, a significant interaction effect between 5-HTTLPR and current relationship problems emerged in the case of current suicidal ideation in the dominant model (Q=0.0218) and in the case of thoughts about death and dying in the dominant (Q=0.0094) and additive models (Q=0.0281). Conclusion: While 5-HTTLPR did not influence previous suicide attempts or interacted with childhood adversities, it did influence current suicidal ideation with, in addition, an interaction with recent relationship problems supporting the involvement of 5-HTTLPR in suicide. Our findings that 5-HTTLPR impacts only certain types of suicide risk-related behaviours and that it interacts with only distinct types of recent stressors provides a possible explanation for previous conflicting findings.